2016
DOI: 10.1149/2.0131701jes
|View full text |Cite
|
Sign up to set email alerts
|

Layered Oxide, Graphite and Silicon-Graphite Electrodes for Lithium-Ion Cells: Effect of Electrolyte Composition and Cycling Windows

Abstract: The electrochemical performance of cells with a Li 1.03 (Ni 0.5 Co 0.2 Mn 0.3 ) 0.97 O 2 (NCM523) positive electrode and a blended silicongraphite (Si-Gr) negative electrode are investigated using various electrolyte compositions and voltage cycling windows. Voltage profiles of the blended Si-Gr electrode show a superposition of graphite potential plateaus on a sloped Si profile with a large potential hysteresis. The effect of this hysteresis is seen in the cell impedance versus voltage data, which are distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 40 publications
5
98
0
3
Order By: Relevance
“…Silicon particle degradation upon repeated (de-)lithiation.-Throughout our previous studies on SiG electrodes 39,46 as well as in the literature, 32,41,43,47 it has been observed that electrodes based on silicon nanoparticles typically show a significantly lower coulombic efficiency in comparison to conventional graphite. However, it can often be seen that the coulombic efficiency upon extended cycling goes through a minimum between ∼20-80 cycles before recovering to higher values again (see Figure 2a and references 39,43,48 ).…”
Section: Resultsmentioning
confidence: 92%
“…Silicon particle degradation upon repeated (de-)lithiation.-Throughout our previous studies on SiG electrodes 39,46 as well as in the literature, 32,41,43,47 it has been observed that electrodes based on silicon nanoparticles typically show a significantly lower coulombic efficiency in comparison to conventional graphite. However, it can often be seen that the coulombic efficiency upon extended cycling goes through a minimum between ∼20-80 cycles before recovering to higher values again (see Figure 2a and references 39,43,48 ).…”
Section: Resultsmentioning
confidence: 92%
“…52 While the lithium oxalate containing LNMO/graphite cells do have a ∼5-10% lower energy density, they are an interesting option for cobalt-free lithium ion battery cells, which may become critical in the future due to the rising cost and geographic concentration of cobalt. 53 Assuming all electrodes used here have the same initial porosity of 35%, the specific volume of electrode (including voids) per gram LNMO increases from 0.44 cm 3 /g LNMO to 0.46 cm 3 /g LNMO or 0.48 cm 3 /g LNMO by adding 2.5 wt% or 5 wt% lithium oxalate, respectively (calculated from electrode compositions given in Table I and bulk densities of 4.4 g/cm 3 for LNMO, 1.8 g/cm 3 for PVDF, 2.2 g/cm 3 for C65 and 2.1 g/cm 3 for lithium oxalate). 55 Accordingly, the oxidation of lithium oxalate leads to a porosity increase from 35% to 38% in the electrodes with 2.5 wt% and to 40% in the electrodes with 5 wt% lithium oxalate.…”
Section: Discussionmentioning
confidence: 99%
“…n CO 2 (el) n CO 2 (total) = V el RTc el V el RTc el + V gas K H [3] where n CO2(total) is the total amount of CO 2 present in the system and V gas is the volume of the cell's gas headspace. Assuming a constant gas volume, as would be the case for a hard-case cell, the pressure buildup can be expressed as 4: p = n CO 2 (total) K H RT V el RTc el + V gas K H [4] On the other hand, in soft pouch cells, gas evolution would typically lead to expansion (or bulging) of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were hoping to improve the reversibility of the silicon composite by balancing the active material of cathode and anode, but obviously, further work is required to optimize the silicon composite anode to work in a full-cell, Li-ion battery as it was pointed out by other researchers. [44][45][46] Moreover, due to the challenges faced with this new type of full cells, it was hard to move to compositions with higher silicon content than 10 wt% until the issues with capacity fade are resolved. This, of course, requires the discovery of new electrolyte additives, binders and other components in the battery.…”
mentioning
confidence: 99%